LATEST TECHNOLOGY PARADIGM: MODERN AGRICULTURAL TECHNOLOGY FOR MILLENNIAL FARMERS - Rusdiana, Rusdiana; Heldawati, Heldawati; Mahdalena, Mahdalena (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This study explores the role of millennial farmers in driving the transformation of the agricultural sector through the adoption of modern technologies. In the context of agriculture that increasingly requires efficiency and sustainability, millennials, with better access and digital skills, show a higher tendency to integrate advanced technologies into their agricultural practices. This study examines how technologies such as precision agriculture, automation, and digital platforms are used by millennial farmers to increase productivity and manage natural resources sustainably. This study also identifies key factors influencing the adoption of agricultural technologies, including economic, social, technical, and environmental aspects. In addition, the role of government policies and support from various parties, such as the private sector, educational institutions, and non-governmental organizations, are analyzed as important catalysts in accelerating technological transformation in this sector. The results of the study indicate that although modern technologies have great potential to improve agricultural efficiency and sustainability, their successful adoption is highly dependent on adequate policy support.